1993
DOI: 10.1111/j.1365-2915.1993.tb00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and description of a virus causing salivary gland hyperplasia in the housefly, Musca domestica

Abstract: A double-stranded DNA virus was isolated from hyperplasic salivary glands of male and female houseflies, Musca domestica L. (Diptera: Muscidae), collected from a dairy in Alachua County, Florida, U.S.A. Sodium dodecyl sulphate (SDS)-polyacrylamide gel electrophoresis (PAGE) of this housefly salivary gland hyperplasia (SGH) virus revealed the presence of two major and eight minor structural polypeptides. Restriction endonuclease analysis indicated that the c. 137 kilobase pair DNA was double-stranded. Weekly, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 31 publications
5
40
0
Order By: Relevance
“…One important difference concerns the pathology and tissue tropism of GpSGHV. GpSGHV induces a characteristic syndrome of SGH in its host, a property shared with two other viruses of Diptera described in Musca domestica (15) and Merodon equestris (6). It also induces lesions in gonads and accessory glands of male and female tsetse flies (38,39,59,60) and in the milk glands of females (61), which may be responsible for mother-to-offspring transmission.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…One important difference concerns the pathology and tissue tropism of GpSGHV. GpSGHV induces a characteristic syndrome of SGH in its host, a property shared with two other viruses of Diptera described in Musca domestica (15) and Merodon equestris (6). It also induces lesions in gonads and accessory glands of male and female tsetse flies (38,39,59,60) and in the milk glands of females (61), which may be responsible for mother-to-offspring transmission.…”
Section: Resultsmentioning
confidence: 96%
“…In reared colonies, however, horizontal transmission facilitated by the membrane feeding technique used for large-scale feeding of tsetse flies (21) may constitute the main route of virus transmission. The SGH syndrome was also observed in two other species of nonhematophagous diptera, the narcissus bulb fly Merodon equestris (6) and the housefly Musca domestica (15).…”
mentioning
confidence: 88%
“…Although both viruses induce SGH, they possess distinct structural and molecular characteristics. Both viruses are enveloped, rod-shaped with a circular dsDNA genome, and both contain a complex of major and minor structural peptides (Coler et al, 1993;Garcia-Maruniak et al, 2008). The MdSGHV, measuring approximately 656550 nm, contains a 124 279 bp genome (~44 mol% G+C content) that codes for 108 methionine-initiated putative open reading frames (ORFs) (Garcia-Maruniak et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The virus was described initially as a nonoccluded, enveloped, rod-shaped, doublestranded DNA virus (7). Feeding bioassays demonstrated that the virus could be transmitted per os to healthy adult houseflies and that infection with the virus was responsible for the salivary gland hypertrophy (SGH) symptoms.…”
mentioning
confidence: 99%